Conservazione e Ricostruzione: la difficile ricerca di equilibrio nella salvaguardia del Patrimonio Mondiale - Fiorani, Donatella (Restauro Archeologico, 2023)
There is a sort of taboo surrounding the topic of reconstruction, at least in Italy. The reasons for the phenomenon are rather easy to explain: as the National Restoration Charters and, in general, the theoretical principles developed in the peninsula have well demonstrated, conservation can only be practiced when the authentic matter of architecture is present, as any reference to restoration will appear arbitrary and unfounded without this. Nevertheless, as the international scenario has expanded and the concept of heritage has taken on a variety of geo-graphical meanings, reconstruction has become increasingly popular. On the one hand, this has been linked to the different conceptions of authenticity that are prevalent especially in non-European contexts, and on the other hand, concerns the need to meet the needs of the population, especially following calamities such as wars and natural disasters. It is intended here to stimulate the development of a specific reflection on the phenomenon of reconstruction by analysing the scenarios related to the phenomenon, so as to respond to UNESCO’s increasing need to make decisions on reconstruction on the base of useful theoretical support.